The Impact of the Distance between School and Downtown on the Result of the National Exam on Geography 2017 - Meyzilia, Arvina; ., Darsiharjo; Ruhimat, Mamat (International Journal of Engineering and Technology, 2018)
There are some factors that will determine the result of National Exam score. One of them is the distance between school and downtown. The schools that are located in the downtown should have higher score compared to the schools located far away from downtown. It is because of the circulation of information around the downtown schools is more rapid than those schools located in far away from downtown. There are some previous research on correlation between studentsâ€™ accessibility to their schools with students achievement, however there no research on correlation between school distance from downtown and students achievement. This research aims to analyze the correlation between school distance to downtown and studentsâ€™ National Exam achievement on geography subject in 2017. This research is a qualitative descriptive research. This research uses documentation and literature study. The result data of this research shows the school in downtown achieved highest National Exam score on geography, however, there is no positive correlation between the mileage to schools and studentsâ€™ achievement. Furthermore, the distance beteween school and downtown does not show a positive correlation. Therefore it could be concluded that there is no correlation between distance and mileage from school to downtown with the National Exam result on geography subject in 2017 at SMA Negeri Kabupaten Bangka (Public Senior High School in Bangka Regency).Â Â